Mimì Aguglia e Marinella Bragaglia alla prova della fotografia - Simona Scattina (Drammaturgia, 2022)
The pictures featuring Mimì Aguglia and Marinella Bragaglia, actresses from the Sicilian dialect theatre, blur the boundaries between stage and life, fiction and reality. The interior and poetic space of the theatrical action is identified with the physical space, discovering, in the geography of a face, in the arcane outline of an expression, the traces of a submerged landscape. Photos that also allow us to explore the way in which the island (and national) theatre was visually narrated from the second half of the 19th century to the very early years of the 20th century. Starting from photographic documents of the time, the contribution will attempt to outline – taking into account a few, but essential, biographical elements – the portrait of these two significant figures of a more general dramaturgy of actresses. Inhabiting the stories of these actresses means attempting to tune «voices and souls, bodies and writings», in a fertile interweaving, according to the indications left by Claudio Meldolesi, between «intimate images», the «level of techniques» and the «level of the given conditions». We will see, going beyond the image of the actress, how the photos become a model of femininity, success or more generally of life (the performer becomes the object of attention far beyond the stage, as an example of woman, wife and mother), among the female spectators.